Late Cretaceous reptilian biota of the La Colonia Formation, central Patagonia, Argentina: Occurrences, preservation and paleoenvironments - Brandoni, Zulma Nelida (2015)
Cropping out on the southeastern margin of the Somún Cura Plateau, the La Colonia Formation (Campanian-Maastrichtian) has yielded, over the last several decades, a varied fossil tetrapod fauna (mammals, ophidians, turtles, dinosaurs, plesiosaurs, anurans). For this study several field trips were carried out specifically to recover reptile remains. Three sections, located on the southeastern slope of the Sierra de La Colonia and in the vicinity of Cerro Bayo, Chubut Province (Argentina), were selected for particular attention. The prospected sections are composed of massive, laminated or heterolithic siltstones and claystones, with scarce and thin intercalations of massive, heterolithic o cross-bedded fine sandstones and of fossiliferous conglomerates. The most abundantly recovered reptiles are terrestrial and freshwater turtles, followed by plesiosaurs and dinosaurs. Among the chelonians, more than 16 specimens of Patagoniaemys gasparinae (Meiolaniformes), three specimens of Yaminuechelys aff. Y. gasparinii (Chelidae), and the remains of a new genus of Chelidae were identified. Among the dinosaurs, theropod metatarsal fragments, an incomplete abelisaurid theropod skeleton, sauropod vertebrae, ankylosaur osteoderms and appendicular fragments of hadrosaurs were found. Among the plesiosaurs there are several well preserved elasmosaurids (including two with associated gastroliths) and a polycotylid (Sulcusuchus erraini). Except for the plesiosaurs, all the reptiles are terrestrial or freshwater taxa. However, analysis of the elasmosaurids indicates they are adult specimens of small body size, which could be related to forms that lived in restricted aquatic environments. Likewise, the polycotylid possesses deep rostral and mandibular grooves, and a conspicuous vascularization and/or innervation, that is consistent with the presence of some associated special sensory structures similar to those known in some cetaceans that inhabit modern rivers and estuaries. Sedimentological analysis suggests that deposition would have been mostly in low-energy restricted environments, like muddy plains, marshes and ponds cut by meandering channels, probably in the central mixed-energy zone within an estuary. This interpretation is consistent with the habitat inferred for the recovered reptiles, as well as with associated foraminifers and with the probable origin of gastroliths found associate with the plesiosaurs.